PENGARUH INTELLECTUAL CAPITAL, KEPEMILIKAN INSTITUSIONAL, DAN LEVERAGE TERHADAP INTEGRITAS LAPORAN KEUANGAN: (Studi Empiris pada Perusahaan Sektor Barang Konsumen Primer yang terdaftar di Bursa Efek Indonesia 2017-2021) - Rachman, Ananda Putri Pratiwi; Handayani, Asih (Politeknik Negeri Ambon, 2023)
This study aims to analyze the effect of intellectual capital, institutional ownership, and leverage on the integrity of financial statements. The population of this study consists of companies operating in the primary consumer goods sector and listed on the Indonesia Stock Exchange between 2017 and 2021. The research sample consists of 25 companies selected by purposive sampling. The data used in this research are financial reports and annual reports. . The analysis was carried out quantitatively, by applying panel data regression analysis using Eviews 12 software, with a significance level of 5%. The results show that there is a positive effect between intellectual capital and institutional ownership on the integrity of financial statements, while leverage has a negative effect on the integrity of financial statements.